Cyclomorphism in Bosmina longirostris (Crustacea:Cladocera) from Lake Ikeda, Japan - Shaharudin Abdul Razak,; Toshio Saisho, (Universiti Kebangsaan Malaysia, 2011)
Zooplankton were sampled in Lake Ikeda at a fixed station every month with the aid of a plankton net in order to observe whether cyclomorphism was exhibited by the neonates of Bosmina longirostris. In Lake Ikeda the relative sizes of the antennules and mucrones of B. longrostris neonates decreased in relation to carapace length from 65% in winter to 50% in summer. Mucrone lengths also decreased from 30% in winter to 20% in summer. Both appendages were inversely correlated with surface temperature of the lake. Predation seems to be one of the reasons why neonates of B. longirostris exhibited seasonal cyclomorphism in their antennule and mucrone